Human Resource Development to Improve the Performance of Village Employees in Developing the Effectiveness of Achieving the Tourism Village Program - Kusuma Agdhi Rahwana; Mila Karmila (Jurnal Riset Ekonomi Manajemen (REKOMEN), 2024)
This study aims to determine the influence of Human Resources Development on the Performance of Village Employees and the Effectiveness of Tourism Village Program Achievement in Cimerak District, Pangandaran Regency. The research method used in this study is a quantitative method with an associative analysis approach (causality) and census. The population in this study amounted to 138 village employees in Cimerak District. The type of data used in this study is primary data obtained through questionnaires. The data testing technique used in this study uses validity tests, reliability tests. Data analysis in this study used path analysis using SPSS software version 25. The results of this study show that Human Resource Development is able to improve the Performance of Village Employees in Cimerak District, Pangandaran Regency in developing the Effectiveness of Tourism Village Program Achievement. Where one of the villages in Cimerak District, namely Masawah Village, there is Madasari Beach which is famous for its Breakwater Beach. With this research, Human Resource Development affects the performance of village employees and the effectiveness of achieving tourism village programs.